Exploratory study of the underutilization of CTSA module services. Issue 1 (10th August 2022) - Elworth, Julie T.; Vaught, Melissa; Harvey, Jillian; Paranal, Rechelle; Zell, Adrienne; El Bcheraoui, Charbel
Abstract: Background/Objective: The Clinical and Translational Science Award (CTSA) program aims to enhance the quality, efficiency, and impact of translation from discovery to interventions that improve human health. CTSA program hubs at medical research institutions across the United States develop and test innovative tools, methods, and processes, offering core resources and training for the clinical and translational research (CTR) workforce. Hubs have developed services across different domains, such as informatics and pilot studies, to provide ad hoc expertise and staffing for local research teams. Although these services can provide efficient, cost-effective ways to cover skills gaps and implement rigorous studies, three CTSAs of varying size found the majority of investigators were single domain service users, likely missing opportunities to further enhance their work. Methods: Through interviews with CTSA service users and a survey of CTSA service managers, this exploratory study aims to identify barriers to using services from multiple modules and solutions to overcome those barriers. Results: Barriers include challenges in finding information about services, unclear or unknown user needs, and users' lack of funding to engage in services. More issues were identified for the largest CTSA. Conclusions: Although this study represents a small subset of CTSA hubs, we anticipate that our findings and proposed solutions will be relevant to the broader CTSA community. This study provides foundational information can use in their own efforts to increase service utilization and methods that can be used for more comprehensive studies that focus on explaining the relationship between CTSA features and rates of single versus cross-module service use.